Relasi Kuasa Pascareformasi dalam Pengelolaan Resor Wisata Nusa Dua - Purnaya, I Gusti Ketut (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
Abstract This article analyses the power relations between three stakeholders involved in the management of the Nusa Dua Tourism Resort, Bali in the seventeen years after thereformation era, between 1998 to the present. It was chosen because after the reformation era, there have been changed inthe nature of power relations among the three stakeholders inthe region, that is between the government (BTDC), investor (hotel manager), and local communities. This study uses the theory of hegemony, the discourse of power/ knowledge, and communication actions was applied eclectic considering the sub-topics discussed related to each other. The analysis ofthe power relations was strengthened by the analysis of thesubtopics of ideologies as a contributing factor to the natureof power relation and the strategy of each stakeholder wastaking in defining their relations to each others. The study shows that the relation of power between BTDC and the local people had changed drastically since the reformation era, from the hegemonic into the negotiative which then changed into the oppositional relation. The article concludes that social and political situation in Bali gave significant impacts to the nature of relationship between tourism stakeholders in Nusa Dua.
Keywords: Nusa Dua Tourist Resort, power relation, hegemony, negotiation, oppositional, Bali